An Analysis of the Effectiveness and Contribution of Regional Original Revenue for Regional Expenditures in Magelang Regency 2015-2019 - Jaka Prasetya; Nuwun Priyono (Program Studi Pendidikan Ekonomi, IKIP Budi Utomo Malang, 2021)
The purpose of this research is to observe in detail related to how the level of effectiveness and contribution of Regional Original Income (PAD) to Regional Expenditures in Magelang Regency in 2015 - 2019. The data used by researchers in conducting this research is secondary data. which comes from a review of the financial information of the Regional Government of Magelang Regency in the 2015-2019 period. This study uses descriptive methods or rules. This study produces several findings which state that the Magelang Regency Government in realizing Regional Original Income in the 2015-2019 period has been considered very effective with the calculation results of an average effectiveness rate of 109.56%. While the PAD contribution to Regional Expenditures remains low because, on average, the rate of contribution (contribution) is only 15.05%.